2016
DOI: 10.1039/c5ja00446b
|View full text |Cite
|
Sign up to set email alerts
|

Determination of tantalum from tantalum oxide nanoparticle X-ray/CT contrast agents in rat tissues and bodily fluids by ICP-OES

Abstract: Accurate and precise means for quantifying Ta in tissues, bodily fluids, and bone is critical in understanding anticipated safety-profiles for tantalum oxide (TaO) nanoparticle-based X-ray/CT diagnostic imaging agents and has prompted the development of three digestion methods which are the focus of this work. Spike recovery studies were employed to evaluate bias, precision, and sample matrix effects in the quantification of Ta in (1) liver, blood and femur by microwave-assisted digestion, (2) urine by open-be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…They must diffuse to the blood, after which they can be excreted via the liver, kidneys, and spleen. [ 9,42 ] For nanoparticles, clearance has been shown to go rapidly from the blood, with less than 1.15% injected dose remaining in the body after 48 h. [ 9 ] Previous in vivo nanoparticle studies have not demonstrated any blurring of device features during sequential CT scans due to dispersed nanoparticles, so the results in long‐term monitoring should be consistent with the data collected during in vivo applications. [ 22 ]…”
Section: Resultsmentioning
confidence: 91%
“…They must diffuse to the blood, after which they can be excreted via the liver, kidneys, and spleen. [ 9,42 ] For nanoparticles, clearance has been shown to go rapidly from the blood, with less than 1.15% injected dose remaining in the body after 48 h. [ 9 ] Previous in vivo nanoparticle studies have not demonstrated any blurring of device features during sequential CT scans due to dispersed nanoparticles, so the results in long‐term monitoring should be consistent with the data collected during in vivo applications. [ 22 ]…”
Section: Resultsmentioning
confidence: 91%
“…They must diffuse to the blood, after which they can be excreted via liver, kidneys and spleen. [9,36] For nanoparticles, clearance has been shown to go rapidly from the blood, with less than 1.15% injected dose remaining in the body after 48 hrs. [9] Previous in vivo nanoparticle studies have not demonstrated any blurring of device features during sequential CT scans due to dispersed nanoparticles, so the results in long-term monitoring should be consistent with the data collected during in vivo applications.…”
Section: Longitudinal Monitoringmentioning
confidence: 99%
“…[9,36] For nanoparticles, clearance has been shown to go rapidly from the blood, with less than 1.15% injected dose remaining in the body after 48 hrs. [9] Previous in vivo nanoparticle studies have not demonstrated any blurring of device features during sequential CT scans due to dispersed nanoparticles, so the results in long-term monitoring should be consistent with the data collected during in vivo applications. [21] The incorporation of nanoparticles within slow degrading polymer matrices is a way to conveniently localize radiopaque markers or implants, bypassing the immediate problems with cellular toxicity of concentrated nanoparticle bolus injections and providing a sustained signal.…”
Section: Longitudinal Monitoringmentioning
confidence: 99%
See 1 more Smart Citation
“…Potential cytotoxicity concerns and fast excretion in native tissues have been raised for bismuth [11] and the highly water-soluble nature of barium sulfate (BaSO4), while commonly used as a clinical gastrointestinal contrast agent, presents hurdles in use with hydrophobic polymers. In contrast, tantalum oxide (TaO x ) nanoparticles are biocompatible and inert [12], and can be differentially synthesized to be compatible with either aqueous media or hydrophobic systems [13].…”
Section: Introductionmentioning
confidence: 99%